2013
DOI: 10.1176/appi.psychotherapy.2013.67.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Countertransference Feelings when Treating Teenagers. A Psychometric Evaluation of the Feeling Word Checklist–24

Abstract: The Feeling Word

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 39 publications
12
38
0
Order By: Relevance
“…This could be due to the therapists overall being highly experienced and the fact that regular group supervision is part of the therapists' work, in which CT is a focus. This is in line with the report of Ulberg et al (18), in which Confident was positively associated with more experience as well as with an increased level of supervision-that is, they found lower levels of Inadequate feelings with more supervision.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This could be due to the therapists overall being highly experienced and the fact that regular group supervision is part of the therapists' work, in which CT is a focus. This is in line with the report of Ulberg et al (18), in which Confident was positively associated with more experience as well as with an increased level of supervision-that is, they found lower levels of Inadequate feelings with more supervision.…”
Section: Discussionsupporting
confidence: 92%
“…The mean scores range from 0.47 (Inadequate) to 1.12 (Idealised) to 2.74 (Confident).. The scores are in a similar range to that seen in many other FWC studies-that is, quite low scores are consistently reported (9,14,17,18). However, the patients in the present study are mainly poorly functioning PD patients, and one might have expected stronger feelings to be reported.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Later, it was extended to a 58-item version to capture more nuanced feelings (Røssberg et al, 2007). Several studies with the FWC-30 or FWC-58 have been conducted in non-forensic psychiatric samples, like patients with bulimia nervosa (Daniel, Lunn, & Poulsen, 2015), phobic disorders (Hoffart & Friis, 2000) and adolescents (Ulberg et al, 2013). In a group of Norwegian psychiatric inpatients in general psychiatry it was found that aggressive and suicidal behavior explained a large proportion of the variance in negative feelings of staff members as measured with the FWC-58 .…”
Section: Measuring Feelings Towards Patientsmentioning
confidence: 99%